Characterization of two conformational forms of the major DNA-binding protein encoded by herpes simplex virus 1. - Knipe, D M (1982)
We have resolved two electrophoretic species of the major DNA-binding protein, infected cell polypeptide 8 (ICP8), encoded by herpes simplex virus 1. In pulse-chase experiments, we observed the conversion of the ICP8a form, the slower migrating species, to the faster migrating form, ICP8b. Thus, the two species appear to be related as precursor-product. The conversion was not due to proteolytic cleavage, because higher concentrations of reducing agents in the sample buffer shifted the faster moving form to the slower moving species. Also, the two forms have identical peptide patterns as analyzed by partial proteolysis in sodium dodecyl sulfate. Thus, the faster moving species appears to be a conformational isomer containing intramolecular disulfide bonds. The functional significance of the two forms of the protein is discussed.